Evaluation of the efficacy and safety of cytoflavin as a neuroprotector based on a systematic review - E. K. Krasova; I. A. Titovich; K. O. Sidorov; S. V. Okovityi (Разработка и регистрация лекарственных средств, 2025)
Introduction. Currently, neurological diseases occupy one of the first places in terms of the DALY (Disability-adjusted life year) index and are the second cause of death in the world. There is a tendency towards rejuvenation and an increase in morbidity. Drug therapy aimed at neuroprotection and improving the restoration of neurological functions according to clinical recommendations includes a succinate-containing drug – Cytoflavin. However, these recommendations are based on a very limited number of studies (4 studies for cytoflavin). Due to the huge amount of work in the field of the use of succinate-containing drugs as neuroprotectors, the lack of quantitative assessment of research results, it seems promising to conduct systematic reviews and meta-analysis in this area.Aim. Evaluation of the efficacy and safety of cytoflavin as a neuroprotector based on a systematic review.Materials and methods. A systematic review of the research results was conducted according to the criteria of PRISMA 2020. The search for publications was carried out using PubMed, Medline databases, as well as Russian scientific electronic libraries eLibrary.Ru and RSCI. Materials were also searched in the systems of the national and international registry of clinical trials.Results and discussion. The review included 18 publications, including a description of the therapy of 10 pathologies of neurological origin. The largest part of the studies was devoted to the treatment of ischemic stroke (n = 4/18; 22.22 %) and manifestations of cognitive dysfunction (n = 5/18; 27.78 %). The pool of materials included studies of various designs, but most of them were represented by open comparative randomized/non-randomized studies. An analysis of the sources showed that the positive effect of the use of cytoflavin and the expediency of including its therapy regimen is noted in all publications. However, many studies have low statistical power due to the small sample sizes of patients, their heterogeneity and incompleteness of providing treatment data and the lack of randomization.Conclusion. According to the results of most clinical studies, it has been shown that the use of cytoflavin is safe, and its administration in neurological diseases of various origins is advisable due to a decrease in the frequency of adverse neurological outcomes in patients. For an objective research result, a meta-analytical assessment of the publications included in the review is required.